Social Media Influencers and Public Trust in Over-the-Counter Medication Recommendations - Daniel Wijaya Santoso; Siti Aurelia Nasution; Ayu Nusriani (Generasi Sains Indonesia, 2026)
This study examines how social media influencers shape public trust in over-the-counter medication recommendations within digital communication environments. Using a qualitative research design, the study collected data through in-depth interviews, digital observation, and document analysis involving active social media users and influencer-generated pharmaceutical content. The findings reveal that influencer credibility, perceived authenticity, and parasocial interaction significantly influence audience trust and self-medication behavior. Audiences tend to trust relatable and emotionally engaging communication more than formal medical authority, particularly when influencers share personal experiences and transparent recommendations. However, concerns regarding hidden sponsorships, misinformation, and commercialization also emerged as important factors affecting public skepticism. The study contributes to digital health communication scholarship and offers practical implications for policymakers, healthcare institutions, and social media regulators in promoting ethical pharmaceutical communication practices.